Enhancement in Bacterial Cellulolytic Enzyme Production Using Acid-Pretreated Banana Peel Waste: A Comparative Evaluation - Khan P.A.; Lal B.; Singh P.; Singh R.; Syed A.; Elgorban A.M.; Verma M.; Mishra P.K.; Verma B.; Srivastava N.; O’Donovan A. (My University, 2025)
Banana peel waste is one of the major contributors in the issue raised from solid waste, however, it can be valorized effectively due to high content of cellulose and hemicellulose. Significant conversion of banana waste includes cellulolytic enzymes and bioenergy production. In the present study, bacterial cellulase was produced using raw banana peel and ripe banana peel under SSF. Additionally, impact of acid pretreatment was investigated as one of strategy to improve cellulolytic enzyme production. A comparative evaluation of raw and ripe banana peels showed that ripe banana peels showed better enzyme production after pretreatment with 0.5% dilute HCl acid. In the series of enhancement of the enzyme production, temperature and pH of the SSF medium were also investigated, and found temperature 35 °C and pH 6.0 were optimum to produce maximum 3.5-U/ml FPA, 39-U/ml BGL, and 54-U/ml EG in 18-h SSF incubation. The study presented eco-friendly waste management to produce industrial enzyme for its promising application in waste valorization and biorefinery area. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.